Evidence for Isolapotamon bauense Ng, 1987 (Decapoda: Brachyura: Potamidae) Being the Largest Recorded True Freshwater Crab in Southeast Asia - Abit, Lirong Yu; A. K., Jongkar; Grinang; Latif, Kamil (Journal of the Bombay Natural History Society (JBNHS), 2022)
No Abstract.